An 'IPCC for Food'? How the UN Food Systems Summit is being used to advance a problematic new science-policy agenda - Jennifer Clapp; Molly Anderson; Maryam Rahmanian; Sofia Monsalve Suarez (IPES-Food, 2021)
This brief demonstrates that: • The calls for a new 'IPCC for Food' originated from a small group of actors whose views have been amplified by a powerful network of organizations, many of which are closely aligned with business and industry. These groups are using the UN Food Systems Summit to promote their 'game-changing' proposal. • Many of the functions of the proposed science-policy interface for food systems are already fulfilled by the High Level Panel of Experts on Food Security and Nutrition in its role vis-à-vis the UN Committee on World Food Security. • Several of the roles envisaged for an 'IPCC for Food' – such as conducting new research with the goal of resolving controversies – could actually undermine a serious and fair consideration of complex issues that must be seen from multiple perspectives. • Unlike the High Level Panel of Experts on Food Security and Nutrition, plans for a new science-policy interface do not appear to involve broad stakeholder consultation and incorporation of different forms of knowledge – elements that should be a fundamental part of good food systems science and are important for legitimacy. • It is unclear to which intergovernmental body the new panel would provide policy advice. This raises important questions about the underlying political ambition of this proposal and its implications for food systems governance. • The Scientific Group of the UN Food Systems Summit, which serves as an 'early experiment' for the new science-policy interface, falls short in several respects: it is non- transparent; is imbalanced in its composition and biased in its perspectives and sources of knowledge; is unreflexive about the relationships between food systems and society; and is pursuing a business-oriented 'technology and innovation' agenda.